Designed a new compensation current control method for three-phase grid-connected photovoltaic inverter - Mohd. Zin, Abdullah Asuhaimi (Asian Research Publishing Network, 2016)
This article proposes a New Compensation Current Control Method for Three-Phase Grid-Connected Photovoltaic Inverter. Our proposed grid-connected power converter consists of a switch mode DC-DC boost converter and an H-bridge inverter. The control method designed to eliminate main harmonics and also is responsible for the injection power to the grid. The proposed control method is comprised of the advance synchronous reference frame method (ASRF). The simulations for three-phase Bridge type inverter have been done in MATLAB/Simulink. To validate the simulation results, a scaled prototype model of the proposed inverter has been built and tested.